Coal mining trends and future prospects: A case study of Eastern Salt Range, Punjab, Pakistan - Ullah, Muhmmad Fahad; Mahmood, Khalid; Akram, Mian Sohail (Journal of Himalayan Earth Sciences, 2018)
Coal is an organoclastic sedimentary rock, composed essentially of lithified plant debris. Coal is an important energy source and is available in all over the world. Pakistan possesses huge coal reserves across the country that can play a pivotal role in development of the country overcoming the energy crises prevalent in four seasons. Government of Pakistan is seriously looking for alternative resources other than hydro and thermal energy to meet the ongoing and growing energy requirements. Most of the world’s lignite deposits are located in Asia. Pakistan is among the top most lignite coal-bearing countries in Asia possessing almost 97% of the coal reserves bearing lignite variety. The rest of the grades are of sub-bituminous to bituminous content. Amongst all the reserves in Asia, 3% are located in Pakistan. The major coal reserves in Punjab are found in Eastern & Central Salt Range and Trans-Indus Range. Most of the region’s coal and carbonaceous coal deposits are located in the Paleocene Patala Formation, with a minor occurrence in the Tobra formation of the Permian age. Mining techniques are being pursued viz; room and pillar method and longwall system that are commonly applied in the areas. Supports are provided without geotechnical evaluation. Timbering is provided as supports in these coal mines. The analysis of accidents shows that roof collapse and fall of side walls are the most common and frequent type of fatal accidents making almost of total accidents.